The Ordeal of the Alien : The Case of a Sudanese â€œLost Boyâ€ in America - Nas, Loes (SARE: Southeast Asian Review of English, 2017)
Stories about refugees, asylum seekers, boat people, illegal aliens and migrants are found almost every day in any newspaper in the world. Not only in economic terms does the world seem to have become global, migration is also playing its part, whether this takes place voluntarily or involuntarily. After more than 20 years of civil war in the southern Sudan, which saw severe displacements and loss of life, approximately 4,000 young men and boys were accepted in 2001 as refugees to the United States. This ended their over ten-year history of flight and migration by foot from southern Sudan via Ethiopia and Kenya to, ultimately, the United States. This group, most of whom have settled in the state of Georgia, has become known as the ’Lost Boys of Sudan’. On arrival in the States, these refugees were given one change of clothes and a three-month guarantee of government support. After that, they had to fend for themselves.